(untitled) (Transport systems and technologies, 2021)
Extension of the service life of a particular passenger railway car can be considered fully justified only if it is justified by the results of scientific and experimental research and approved by the relevant administrative documents of Ukrzaliznytsia the service life limit for wagons of this type. The existing method of technical diagnostics of passenger railway cars does not allow to fully assess the probability of extension of the service life of the car, because it does not take into account the peculiarities of damage to structural elements during operation. In the article the sequence of research of stresses in elements of a frame of a body of the passenger car of construction of KVN on the basis of standard tests is considered. The task of the study is to determine the sequence of calculation of stresses in the frame elements of the passenger car body of KСР (Kryukiv Carriage Plant) with a service life exceeding 41 years from the date of manufacture to assess strength and fatigue resistance by technical diagnostics and standard tests. It is concluded that the condition of the load-bearing metal structures of cars after long operation does not approach the limit. The residual resource was set at one of the minimum calculated values. If the results of calculations show that the resource is exhausted, the residual service life is determined by the results of bench tests for fatigue. The obtained practical and theoretical results make it possible to extend the service life of cars beyond that set by the manufacturer.